Ask a question
0 0


Tutors, please sign in to answer this question.

2 Answers


4^(2x-1)=5^(x+2) <==Is this what you want?

Take ln,
(2x-1)ln4 = (x+2)ln5
Solve for x,
x = (2ln5+ln4)/(2ln4 - ln5) = 3.95922
This is a calculated answer:
x = 0.6318


Dear Galeboe:
When I interpreted the problem, I interpreted it as

(42x) - 1 = (5x) + 2

which, of course is quite different from the way Robert interpreted the question, to wit

4(2*x-1) = 5(x+2)

This is why learning to use parentheses and brackets is so important.  Chances are I was trying to solve the wrong system of equations.